ANALISIS PENGARUH MOTIVASI KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Empirik Pada PT. Asuransi Umum Bumiputera Muda 1967 Cabang Pontianak) - Latifah Latifah (Universitas Bina Sarana Informatika, 2016)
This study entitled Analysis of Influence Motivation Work To Performance With Job Satisfaction as an intervening variable (Empirical Study at PT. Asuransi Umum Bumiputera Muda 1967 Branch Pontianak) to analyze the effect of work motivation on employee performance and job satisfaction as an intervening variable in PT. General Insurance Bumiputera Muda 1967 Branch Pontianak. This study uses a variable work motivation to analyze the influence on employee performance. In addition, this study also uses job satisfaction as an intervening variable to analyze the effect of indirect work motivation on employee performance. Methods of data collection using census sampling methods respondents are all employees except the leadership totaling 31 people. Data was collected using a questionnaire method is to give a list of questions directly to the respondents. Data analysis techniques in this study using path analysis which is operated by SPSS. The results showed a positive relationship between motivation and performance, the positive relationship between job satisfaction and performance as well as the positive relationship between motivation and job satisfaction. path analysis found that that motivation does not affect the performance through Job satisfaction. So it can be concluded that job satisfaction does not become an intervening variable between Motivation on Performance.